Implementation of SEIP (Spiritual, Emotional Intellectual and Physical) Method in Learning for Students in Junior High Schools - Mendrofa, Kristiana; Lay, Sergius; Harefa, Tetinia (Indonesian Journal Publisher, 2024)
This study aims to determine what the SEIP method means and how teachers apply it in learning for students in junior high schools. This study applies a literature study method through the collection of library sources to obtain research data. Library data collection is limited to library collection materials only without requiring field research. In this case, the author collects relevant reference sources, such as books, documents, the Indonesian dictionary, and so on. Literature search with the keywords